The Impact of Leverage on Earnings Per Share: A Study of Selected Petroleum Companies in India - Ahmed Mahdi Abdulkareem; Priyanka Dineshgiri Meghanathi (Journal La Bisecoman, 2020)
The main purpose of this article is to study the impact of leverage on earning per share of selected petroleum companies in India. The article also aims to examine the correlation between three types of leverage with earning per share and to know more about the leverage and petroleum industry in India. The most appropriate Parametric and Non parametric tests are employed and the analysis of data is presented through different graphs and tables. This article comes across to draw a comparison between the degree of combined leverage and earnings per share of selected petroleum companies during the study period.